ANALISIS FRAMING KONTROVERSI ARCANDRATAHAR DALAM PORTAL BERITA ONLINE DETIK.COM - Anggara Putra, I Gusti Agung Putu; Amanda Gelgel, Ni Made Ras; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2019)
ABSTRACT   There was controversy   of Arcandra Tahar that dismissed as minister by Jokowi because of dual nationality On 15 August 2016, but then on October 14 Arcandra was appointed again as vice minister of ESDM on the kabinet kerja .The goal of this research is to  describe how the issue was framed by detik.com. this research is using descriptive qualitative Approach. Data resource are the news in the online media detik.com from  13 August 2016 until 15 October 2016. The Method that used in this research is  framing analysis  by Robert N. Entman. The analysis is divide in 4 phase there are: (1) define problem, (2) diagnose causes, (3) make moral judgment, (4) treatment recommendation. The result of this research is news about the issue of Arcandra Tahar at the ministry  on online media detik.com  tend to be about criticism of the president Joko Widodo’s decision.   Keywords: framing, controversy, Arcandra Tahar, detik.com